Increased IL‐17‐expressing γδ T cells in seborrhoeic dermatitis‐like lesions of the Mpzl3 knockout mice. Issue 12 (27th November 2018) - Wikramanayake, Tongyu C.; Hirt, Penelope; Almastadi, Maram; Mitchell, Hunter; Tomic‐Canic, Marjana; Romero, Laura; Garcia, Denisse; Strbo, Natasa
Abstract: Seborrhoeic Dermatitis (SD) is a common inflammatory skin disorder, but its molecular pathogenesis remains elusive. Previously, we have established the Mpzl3 knockout (−/−) mice as a model for SD. In this study, we focused on early phases of skin inflammation and determined the cytokine profiles and identified immune cell types in the lesional skin in the Mpzl3 −/− mice. Using flow cytometry, we detected a significant increase of CD45+ leucocytes, CD3+ T lymphocytes and especially γδ T cells but not αβ T cells in the lesional skin compared to control. We also detected high levels of IL‐17 and determined that the γδ T cells were a major contributing source. CD3+ and γδ T cell localization in the skin was verified by indirect immunofluorescent staining. Since neither γδ T cells nor IL‐17 had been implicated in SD, our study provides novel insights into the role of MPZL3 in the pathogenesis of SD‐like skin inflammation.